Case report: Heterozygous variation in the IGHMBP2 gene leading to spinal muscular atrophy with respiratory distress type 1 - Zhou, Chaoai; Chen, Zefu; Chen, Qiqing; Feng, Xiaowei (Frontiers in Neurology, 2024)
A rare autosomal recessive genetic disease is spinal muscular atrophy with respiratory distress type 1 (SMARD 1; OMIM #604320), which is characterized by progressive distal limb muscle weakness, muscular atrophy, and early onset of respiratory failure. Herein, we report the case of a 4-month-old female infant with SMARD type 1 who was admitted to our hospital owing to unexplained distal limb muscle weakness and early respiratory failure. This report summarizes the characteristics of SMARD type 1 caused by heterozygous variation in the immunoglobulin mu DNA binding protein 2 (IGHMBP2) gene by analyzing its clinical manifestations, genetic variation characteristics, and related examinations, aiming to deepen clinicians’ understanding of the disease, assisting pediatricians in providing medical information to parents and improving the decision-making process involved in establishing life support.